Effect of Pre-cooler on Supply and Return Air of Air Curtain in Display Cabinet - Zhang Wenhui; Gong Yi; Lu Yanli (Zhileng xuebao)
This study focused on a vertical open-type display cabinet with double air curtain, and investigated the effect of pre-cooler on supply and return air of air curtain in display cabinet. The experimental investigation was undertaken in the test room with temperature of 25℃ and relative humidity of 60% to characterize the effect of pre-cooler on supply and return air of air curtain in display cabinet. The results showed that: the temperature of the supply air was not obviously elevated, and the return air temperature was reduced by 5℃; the inner supply air and the return air relative humidity of air curtain changed little, the outer supply air relative humidity dropped from 69% to 60%; and the enthalpy of outer supply air kept a fixed value, and the enthalpy of the return air decreased by 21.4%. The decreases of return air temperature and enthalpy could lead to significant decrease in the display cabinet load.